2002
DOI: 10.1016/s1388-9842(02)00006-5
|View full text |Cite
|
Sign up to set email alerts
|

Self‐rating of quality of life provides additional prognostic information in heart failure. Insights into the EPICAL study

Abstract: Background:The relationship between quality of life (QoL) and survival have been poorly investigated. The aim of this study was to determine the value of QoL score as a prognostic factor in a prospective cohort of patients with advanced chronic heart failure (CHF). Methods: QoL assessment was performed with a generic questionnaire: the Duke Health Profile (DHP) and a disease-specific instrument: the Minnesota Living With Heart Failure Questionnaire (LIhFE), in a sample of 108 patients registered in the EPICAL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
136
3
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 32 publications
13
136
3
6
Order By: Relevance
“…Studies of heart failure patients that have used other measures of self-reported health status, such as the Minnesota Living with Heart Failure Questionnaire, the Seattle Angina Questionnaire, or the Nottingham Health Profile, have generally found that global and/or physical health status scores significantly predict mortality in multivariate analyses, but that the relationship between mental or emotional health and mortality varies across studies [10][11][12][13][14][15]. One recent study reported that after controlling for cardiac risk factors and symptoms of depression, mortality was not related to the SF-36 PCS, the SF-36 MCS, or the clinical summary score of the Kansas City Cardiomyopathy Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of heart failure patients that have used other measures of self-reported health status, such as the Minnesota Living with Heart Failure Questionnaire, the Seattle Angina Questionnaire, or the Nottingham Health Profile, have generally found that global and/or physical health status scores significantly predict mortality in multivariate analyses, but that the relationship between mental or emotional health and mortality varies across studies [10][11][12][13][14][15]. One recent study reported that after controlling for cardiac risk factors and symptoms of depression, mortality was not related to the SF-36 PCS, the SF-36 MCS, or the clinical summary score of the Kansas City Cardiomyopathy Questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-reported health status has been shown to independently predict adverse outcomes, including mortality, in studies of patients following coronary artery bypass graft surgery [4], with stable coronary artery disease [9], and with heart failure [10][11][12][13][14][15]. Two studies of heart failure patients included symptoms of depression as a covariate, however, and both found that health status no longer predicted survival after controlling for depressive symptoms [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CCM clinical studies show an improvement in pVO2 which in the literature has been shown to be associated and to predict outcomes such as hospitalizations, mortality and quality of life in heart failure patients [56][57][58][59][60][61][62][63][64][65] . In particular, a recent study has shown that even modest improvements in pVO2 levels are leading to better health status and hospitalization and mortality rates 60 .…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, better quality of life has also been shown to predict hard health outcomes like death and hospitalizations. A recent study showed that a 10 point decrement in the MLWHFQ was associated with a 23%-36% change in the risk of death or hospitalization for HF and hence it was recommended that quality of life is a predictor of survival and hospitalizations 61 . Hence for all three intermediate outcomes for which CCM trials have shown an improvement there is evidence that their improvement leads to hospitalization and mortality benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more studies are needed to understand the associations between the pathology of HF and symptoms and the effects of HF on patients' QOL 6 . Many efforts have been made by the scientific community to correlate the subjective and objective aspects of HF 5,7 . These considerations could help health professionals to outline strategies to manage this dysfunction, not only focused on objective goals, but also on the patients' expectations.…”
Section: Introductionmentioning
confidence: 99%